2014
DOI: 10.5858/arpa.2013-0450-oa
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outpatient Phlebotomy Staffing: Tools to Assess Staffing Needs and Monitor Effectiveness

Abstract: Context.-Short patient wait times are critical for patient satisfaction with outpatient phlebotomy services. Although increasing phlebotomy staffing is a direct way to improve wait times, it may not be feasible or appropriate in many settings, particularly in the context of current economic pressures in health care.Objective.-To effect sustainable reductions in patient wait times, we created a simple, data-driven tool to systematically optimize staffing across our 14 phlebotomy sites with varying patient popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…In many countries, same day access to phlebotomy is expected and provided [ 28 ], yet both patients and staff at our study practices previously reported regular and frequently lengthy waits for an appointment with a phlebotomist [ 6 , 7 ]. Some of the failure to match practice resource to patient need can be attributed to the variability of demand inherent in healthcare provision, and can be mitigated by strategic management interventions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, same day access to phlebotomy is expected and provided [ 28 ], yet both patients and staff at our study practices previously reported regular and frequently lengthy waits for an appointment with a phlebotomist [ 6 , 7 ]. Some of the failure to match practice resource to patient need can be attributed to the variability of demand inherent in healthcare provision, and can be mitigated by strategic management interventions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each specialist visit was estimated to be 122 min in average duration. This assumes a slightly longer time with the clinician (21 min) vs. a non-specialist physician (20 min), as studied by Shaw et al [39] Hospitalization (inpatient)Cardiac cases: $882.56Non-cardiac cases: $554.75Based on the $252.16-per-day value calculated by the FDA [36] and the estimated length of stay for cardiac-related hospital stays and non-cardiac stays from a 2014 study by Shaw et al (3.5 days for cardiac cases; 2.2 days for non-cardiac cases) [39] ED visit$141.84Estimated based on a 4.5-h duration and an average value of an hour’s lost work time of $31.52 per hour [37] Laboratory tests and imaging$18.48From an estimated 15 min of time required for a blood draw by a phlebotomist [40], plus an assumed 37 min of travel to the laboratory site (much like a physician office [38]), an average laboratory visit would take 52 min. Borrowing from the estimated time and cost of a physician visit above (121 min), the cost of the laboratory visit was calculated at $18.48

ED emergency department, FDA Food and Drug Administration, GI gastrointestinal, ob/gyn obstetric-gynecologic, TSH thyroid-stimulating hormone, T3 , triiodothyronine, T4 thyroxine

…”
Section: Methodsmentioning
confidence: 99%
“…Lost productivity was calculated at a rate of $31.52/hour based on government and published sources ( Table 2). From an estimated 15 minutes required for a blood draw by a phlebotomist, [41] plus an assumed 37 minutes of travel to the laboratory site (similar to a physician's office), [38] an average laboratory visit would take 52 minutes. Borrowing from the estimated time and cost of a physician visit noted above (121 minutes), the cost of the laboratory visit was calculated at $18.48.…”
Section: Emergency Department (Ed) Visitmentioning
confidence: 99%